Magnetic nanoparticles: versatile materials with applications in catalysis - Menezes, Fernando Lima de (2024)
This doctoral thesis presents a comprehensive exploration of catalysis, encompassing advanced oxidative processes (AOPs) and enzyme immobilization strategies using novel nanocatalysts. In the first work, sulfate-based AOPs, known for their effectiveness in degrading refractory organic pollutants, were enhanced through the application of carbon-coated FeCo nanoparticles (NPs). The hydrothermal synthesis of this material, based on the polyol method, led to the acquisition of well-characterized NPs with a predominant FeCo phase achieved at specific [OH-] / [Metal] = 26 and [Fe] / [Co] = 2 ratios. The NPs exhibited a spherical morphology with agglomerates of varying sizes and saturation magnetization significantly influenced by the iron proportion in the reaction system. Optimized catalytic conditions for Rhodamine B degradation were 5.0 mg of NPs, 2 mM PMS, pH 7.0, and a 20-minute reaction time, showcasing the potential of the FeCo catalyst in sulfate-based AOPs. Despite its effectiveness, concerns about metal leaching were identified, necessitating future refinement. The second work focused on the synthesis of magnetite nanoparticles coated with L-cysteine as a support matrix for the immobilization of Candida antarctica Lipase A (CALA). Employing a combination of physical interactions and covalent bonding, the synthesized Fe3O4@LC-GLU-CALA system exhibited superior immobilization yield and specific activity compared to physical adsorption. Characterization techniques confirmed the successful synthesis and immobilization processes, and the biocatalyst displayed enhanced activity under various pH conditions. Notably, thermal and pH inactivation studies revealed the robustness of the system, surpassing the half-life of free CALA by more than 8 times at pH 10. The Fe3O4@LC-GLU-CALA system thus emerges as a promising biocatalytic matrix with potential applications in biodiesel production and ester synthesis and pharmaceutical precursors. Collectively, this thesis contributes to the design of novel environmental remediators and nanocatalysts in the pursuit of sustainable and efficient catalytic processes.